Duke activity status index is not predictive of outcomes after kidney transplantation: a retrospective observational study - Ruth Fergie; Alexander P. Maxwell; Aisling E. Courtney; Michael Corr; Stephen O’Neill; Emma L. Cunningham (BMC Nephrology)
Abstract Background Reduced functional capacity increases the risk of adverse outcomes after kidney transplantation. The Duke Activity Status Index is a measurement of physical function, previously reported as being predictive of adverse outcomes after major non-cardiac surgery. This study assessed the ability of the Duke Activity Status Index to predict adverse outcomes for patients undergoing kidney transplantation. Methods Adult kidney transplant recipients with a Duke Activity Status Index calculated at time of listing for transplantation in Northern Ireland between 2019 and 2024 were analysed. Dichotomous outcomes (delayed graft function, unplanned critical care admission, 30-day hospital re-admission, 30-day severe postoperative complication, 30-day cardiovascular complication) were analysed using multivariate logistic regression. Post-transplant length of stay was assessed using multivariate linear regression. All-cause mortality and death-censored graft loss were evaluated using Cox proportional hazard regression models. Results Data was available for 408 kidney transplant recipients. Duke Activity Status Index was not predictive of delayed graft function (aOR 0.99 (95% CI 0.66–1.01) p = 0.359), unplanned critical care admission (aOR1.00 (95% CI 0.97–1.04), p = 0.866), length-of-stay post-transplant, 30-day hospital re-admission (aOR1.01 (95% CI 0.99–1.03), p = 0.457), 30-day severe postoperative complication (aOR 1.01 (95% CI 0.99–1.03) p = 0.489), 30-day cardiovascular complication (aOR 0.99 (95% CI 0.93–1.06), p = 0.850), all-cause mortality (aHR 1.00 (0.96–1.04), p = 0.89) or death-censored graft loss (aHR 0.97 (95% CI 0.93–1.01), p = 0.14). Conclusions In this cohort, the Duke Activity Status Index was not an independent predictor of short or long-term adverse outcomes following kidney transplantation. These findings suggest that the Duke Activity Status Index may have limited utility in assessing functional capacity in waitlisted kidney transplant candidates. Trial registration Not applicable.